Flora costaricensis. Family #39 Orchidaceae: Tribe Cymbidieae: Subtribe Zygopetalinae - Pupulin, Franco (2010)
Although they only represent a small portion (around four percent) of the Costa Rican orchid flora, species of Zygopetalinae are frequently grown (and often avidly collected) for horticultural purposes, and their study is crucial to understanding distribution patterns and species frequency as the first step to establish conservation priorities. Among the genera of Zygopetalinae, Dichaea constitutes a particularly common element in any type of vegetation in the country, and its taxonomic treatment should have a certain utility to field botanists working in Costa Rica. Sixteen genera (including a natural hybrid genus) and 60 species are treated. The work was based on direct examination of the available specimens deposited at AMES, CR, INB, K, M, SEL, USJ, and W; the spirit collection of Lankester Botanical Garden (JBL-Spirit); and scrutiny of digital images fromthe collections kept at F, NY, MO, and US. To ensure nomenclature stability, many of the Costa Rican taxa in the group were recently typified, and additional lectotypes are selected here for Cryptarrhena guatemalensis Schltr. (AMES), Kefersteinia subquadrata Schltr. (AMES), and Warczewiczella caloglossa Schltr. (AMES). Many of the descriptions of individual species are based on those appearing in recent generic revisions by the author; they include the observed variations among specimens native from Costa Rica. All the treated taxa are illustrated with one or more ink illustrations. With the exceptions of D. acostae Schltr., D. gracillima C.Schweinf., and D. gomez-lauritoi Pupulin, which are known only from the dried material of the type collections, the illustrations of all the remaining taxa were prepared by the author on the basis of living specimens with the aid of a stereomicroscope fitted with a drawing tube. As in the previous volume of this series on Costa Rican Orchidaceae, the illustrations are arranged according to their occurrence in the keys to facilitate the comparison of closely allied taxa.